1999
DOI: 10.1074/jbc.274.50.35375
|View full text |Cite
|
Sign up to set email alerts
|

Utrophin Lacks the Rod Domain Actin Binding Activity of Dystrophin

Abstract: We previously identified a cluster of basic spectrinlike repeats in the dystrophin rod domain that binds F-actin through electrostatic interactions (Amann, K. J., Renley, B. A., and Ervasti, J. M. (1998) J. Biol. Chem. 273, 28419 -28423). Because of the importance of actin binding to the presumed physiological role of dystrophin, we sought to determine whether the autosomal homologue of dystrophin, utrophin, shared this rod domain actin binding activity. We therefore produced recombinant proteins representing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
58
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(63 citation statements)
references
References 50 publications
5
58
0
Order By: Relevance
“…These deletions result in a truncated dystrophin that lacks fully functional spectrinlike repeats 17 and 18. Previous studies indicated that spectrinlike repeat 17 is localized to the second actin binding domain of dystrophin (Amann et al, 1999) and is also important for anchoring neuronal nitric oxide synthase (nNOS) to the sarcolemma (Lai et al, 2009). Moreover, both spectrin-like repeat 17 and 18 can bind anionic phospholipids (Legardinier et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These deletions result in a truncated dystrophin that lacks fully functional spectrinlike repeats 17 and 18. Previous studies indicated that spectrinlike repeat 17 is localized to the second actin binding domain of dystrophin (Amann et al, 1999) and is also important for anchoring neuronal nitric oxide synthase (nNOS) to the sarcolemma (Lai et al, 2009). Moreover, both spectrin-like repeat 17 and 18 can bind anionic phospholipids (Legardinier et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The actin-filament binding activity of spectrin-like repeat 17 (Amann et al, 1999) combined with the fact that dystrophin binds filamentous actin composed of different actin isoforms with similar affinities (Renley et al, 1998) led us to hypothesize that spectrinlike repeat 17 might also interact with  cyto -actin. Although we did not detect  cyto -actin on peeled sarcolemma (Rybakova et al, 2000), another study showed sarcolemmal localization of  cytoactin on an in situ skeletal muscle preparation (Lubit and Schwartz, 1980).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, ClC-2 does not possess typical actin-binding motifs such as those present in actinin. However, the present studies in itro suggest that the N-terminus of ClC-2 can interact with actin (K d 0.8 µM) with an affinity for actin similar to that of dystrophin [23]. Further, because the interaction between the N-terminus peptide and F-actin is modified by ionic strength, the interaction might occur via electrostatic interactions.…”
Section: Discussionmentioning
confidence: 73%
“…Further, the acidic C-terminus of band 3 can interact specifically with carbonic anhydrase [27]. Moreover, dystrophin, the membrane protein that is defective in Duchenne muscular dystrophy, has been shown to interact with actin via a series of basic repeats within its rod domain ; this interaction is sensitive to increasing ionic strength [23]. This interaction is thought to be important for normal arrangement of the actin cytoskeleton.…”
Section: Discussionmentioning
confidence: 99%
“…24,25 One difference between them is that the rod domain actin-binding site of dystrophin is not present in utrophin. 26 Nevertheless, Rybakova et al 27 showed that overexpression of utrophin in mdx muscle rescued the defective link between costameric actin filaments and the sarcolemma. They concluded that, even if molecular epitopes differ between the two proteins, utrophin and dystrophin seem to be functionally interchangeable actin-binding proteins.…”
Section: Discussionmentioning
confidence: 99%